2014
DOI: 10.1007/s11661-014-2437-4
|View full text |Cite
|
Sign up to set email alerts
|

Depth Dependence of Nanoindentation Pile-Up Patterns in Copper Single Crystals

Abstract: A study of the dependence of nanoindentation pile-up patterns on the indentation load and crystallographic orientation is presented. Three different orientations-(001), (011), and (111)-of single crystal copper were investigated. Experiments were conducted on a CSM ultrananoindentation tester using a Berkovich tip. The topographic images were obtained using an atomic force microscope. The evolution of pile-up patterns with different applied loads was observed. The results show that for applied loads equal to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
(41 reference statements)
2
13
0
Order By: Relevance
“…We tentatively attribute this effect to different mechanisms and modes of deformation that take place at low (down to hundred nanometers) and large (few hundreds nanometers) penetration depths, as it has been mentioned at the end of BSpecification of the Contact Area with Use of Post-Mortem Method^section, c.f. [41]. This effect can be explained by the fact, that for the lowest loads the motion of dislocations is rather random and is not restrained by the slip planes.…”
Section: Comparison Of Hardness Values Specified With Different Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…We tentatively attribute this effect to different mechanisms and modes of deformation that take place at low (down to hundred nanometers) and large (few hundreds nanometers) penetration depths, as it has been mentioned at the end of BSpecification of the Contact Area with Use of Post-Mortem Method^section, c.f. [41]. This effect can be explained by the fact, that for the lowest loads the motion of dislocations is rather random and is not restrained by the slip planes.…”
Section: Comparison Of Hardness Values Specified With Different Methodsmentioning
confidence: 97%
“…The evolution of the surface topography in the vicinity of residual imprints shown schematically in Fig. 8, was presented more in detail in [41]. In that work the evolution of pile-ups patterns for different directions of indentation performed with Berkovich tip and for large range of loads was studied.…”
Section: ~620 Nmmentioning
confidence: 99%
“…It has been demonstrated that different materials can be differently deformed in the proximity of the contact point. Therefore, these deformations cannot be correlated to the applied load but only to the intrinsic material properties [50]. …”
Section: Working Principles and Basic Toolsmentioning
confidence: 99%
“…Moreover, topographic measurements taken with a scanning tunnelling microscope revealed a significantly higher pile-up on the (100) surface compared with the other two planes tested, namely (110) and (111). Wang et al [14] and Kucharski et al [15] reported an out-of-plane displacement mechanism on the primary slip plane on indentations performed with a conical and Berkovich indenter, respectively. Their experimental data concluded that at low loads, the angular position of the pile-up patterns first correspond with the tip geometry and as the load is increased, the position rotates about the indentation axis until at sufficiently deep indentation depths, the symmetry of the pile-up patterns correspond with the crystallographic orientation of the indented surface, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the 101 , 011 and 110 directions on a (111) surface. Surprisingly, although it is typically accepted that the sinking-in deformation mode is predominant in materials with a high strain hardening behaviour [16], such as the copper studied by Wang et al [14] and Kucharski et al [15], the occurrence of sinking-in was not reported in these studies, instead, the piling-up of material was explained [14] by the rather small local strain hardening resulting from the activation of only a small set of slip systems that accounts for most of the local deformation.…”
Section: Introductionmentioning
confidence: 99%